Academic achievement growth and differential association on proficiency levels - Yang-Boon Kim; Shin, Hyejin (KEDI journal of educational policy, 2018)
The purpose of this study was to explore the differential association to investigate the variables affecting the achievement growth of student, by students’ performance proficiency levels using the Korea Education Longitudinal Study (KELS) 2013. Applying a two-level hierarchical linear model, this study explored student- and school-level factors affecting the achievement growth. This study found that the school average socioeconomic status (SES) showed a significant interaction effect with each level on growth of students’ achievement scores in most subjects. Among student process variables, reading enjoyment showed a significant interaction effect on most levels of fifth grade students’ Korean, advanced levels in English, and below basic levels in Math. Regarding school process variables, while the teacher’s interaction variable showed a positive effect on advanced students in English, it showed inconsistent results by levels of each subject by affecting negative impacts on all levels except the basic level in Korean. This study pointed out that while there was overall achievement growth in all subjects including Korean, English, and Math, proficient and advanced levels of fifth grade in Korean and advanced level students in Math showed declines in average scores. Further, the factors affecting improvements of academic achievement were different by subjects and academic achievement levels. Therefore, appropriate actions for subjects and achievement proficiency levels to improve student achievement should be supported differently.